Recent Advances in Dermatitis Herpetiformis - Kimiko Nakajima (Clinical and Developmental Immunology)
Dermatitis herpetiformis is an autoimmune bullous disease that is associated with gluten sensitivity which typically presents as celiac disease. As both conditions are multifactorial disorders, it is not clear how specific pathogenetic mechanisms may lead to the dysregulation of immune responses in the skin and small bowel, respectively. Recent studies have demonstrated that IgA and antibodies against epidermal transglutaminase 3 play an important role in the pathogenesis of dermatitis herpetiformis. Here, we review recent immunopathological progress in understanding the pathogenesis of dermatitis herpetiformis.